Long-term effectiveness and tolerability of vagal nerve stimulation in adults with intractable epilepsy: a retrospective analysis of 100 patients. (April 2013) - Ching, Jared; Khan, Sadaquate; White, Paul; Reed, Judith; Ramnarine, Devindra; Sieradzan, Kasia; Sandeman, David
Abstract Data for 100 vagal nerve stimulation (VNS) patients were collected and analysed retrospectively. The mean seizure reduction was 17.86% (n = 67) at 6 months, 26.21% (n = 63) at 1 year, 30.43% (n = 53) at 2 years, 48.10% (n = 40) at 3 years, 49.44% (n = 32) at 4 years, 50.52% (n = 35) at 5 years, 45.85% (n = 31) at 6 years, 62.68% (n = 25) at 8 years, 76.41% (n = 9) at 10 years, 82.90% (n = 4) at 12 years. Evidence of statistical significance for mean seizure reduction over time was strong with all p values less than 0.05 except at 12 years (p = 0.125) where the sample size was small (n = 4). Mean seizure reduction was 49.04% and 51 (51%) patients were considered responders, defined as a 50% or more reduction in seizure frequency. Twenty-one (21%) patients suffered surgical complications. Of these 15 patients were self-limiting and 6 patients were irreversible or required a device revision. Fifty patients (50%) suffered from side-effects, while vagal stimulation cycled on (VNS on) post-operatively. However, of these, only one patient suffered from intolerable side effects requiring the device to be switched off temporarily. This study demonstrates the long-term efficacy in seizure reduction with the use of VNS. Complication rates and tolerability did not deviate greatly from that previously reported, indicating that VNS is a safe and effective treatment for seizure reduction in intractable epilepsy.